Changes in the parameters of the rectoanal inhibitory reflex in children with functional constipation and large rectum - Pop, Daniela; Tătar, Simona; Fufezan, Otilia; Farcău, Dorin (Medicine and Pharmacy Reports, 2021)
Background. Abdominal ultrasound and anorectal manometry are part of the investigations used to assess children with functional constipation. This study aimed at assessing the changes in the characteristics of the rectoanal inhibitory reflex (RAIR) in children with functional constipation and correlating them with the dimensions of the rectum, measured by abdominal ultrasound. A secondary objective was to compare the rectum size in children with and without constipation. Method. We retrospectively reviewed the clinical data and investigations results of 51 children (mean age±standard deviation (SD) =5.8±3.5 years) with functional constipation who came to our clinic between January 2013 and February 2020. The assessment of these patients included both the assessment of the transverse diameter of the rectal ampulla by abdominal ultrasound and anorectal manometry. The studied parameters of RAIR were: the minimal volume of air necessary to induce RAIR, in all the patients with functional constipation, and in 20 of them, relaxation time, latency and relaxation percentage. A control group was formed of 27 children (mean age±DS=5.1±4 years) without digestive diseases and with normal intestinal transit, who were assessed by abdominal ultrasound. Results. The mean value ±SD of the volume of air necessary to induce RAIR was 21.9±12.1 cm3 air. There was no correlation between the rectum transverse diameter and the minimal air volume that triggered RAIR (r=-0.01, p=0.94). The mean value ±SD of the transverse diameter of the rectum in patients with functional constipation was 39±14 mm, and in children without constipation 26±6 mm (p<0.05). The mean duration of the symptoms in children with functional constipation was 2.8 years. Conclusions. There were no correlations between the volume of air that induced the RAIR and the transverse diameter of the rectum in children with functional constipation. The transverse diameter of the rectum was increased in children with long-term functional constipation.